The Effect of Using Teams Games Tournament (TGT) Type Cooperative Learning Model Assisted by Destination Media to Improve Students' Learning Outcomes on Buffer Solution Material - Nabilla Suri Ayuandiva; Ani Sutiani (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
The Effect of Using Teams Games Tournament (TGT) Type Cooperative Learning Model Assisted by Destination Media to Improve Students' Learning Outcomes on Buffer Solution Material. This study aims to determine the effect of the TGT type cooperative learning model assisted by learning media on student learning outcomes in buffer solution material. This research was conducted at MAN 2 Model Medan in the even semester of the 2024/2025 academic year. The method used was a quasi-experimental with a non-equivalent control group design. The research sample consisted of class XI-F1 G as the control class and XI-F1 F as the experimental class selected by purposive sampling. Hypothesis I testing was carried out using the Independent Sample T-Test, with the results of the study showing a sig value of 0.00 <0.05, which means that the hypothesis (Ha) is accepted and (H0) is rejected. Hypothesis II testing was carried out using the One Sample T-Test, with the results showing a sig value of 0.00 <0.05, which indicates that there is a positive student response to the TGT type cooperative learning model using destination media on buffer solution material on student learning outcomes, which means that the Hypothesis (Ha) is accepted.